2022
DOI: 10.1111/eos.12855
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of molar agenesis associated with p.P20L and p.R77Q variants in PAX9

Abstract: Nonsyndromic tooth agenesis is associated with variants in several genes. There are numerous genotype-phenotype publications involving many patients and kindreds.Here, we identified six Thai individuals in two families with nonsyndromic tooth agenesis, performed exome sequencing, and conducted functional experiments. Family 1 had four affected members carrying the heterozygous PAX9 variant, c.59C>T (p.Pro20Leu). The p.Pro20Leu was previously reported in two families having four and three affected members. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Tooth development is regulated by several genes and signaling pathways [3] . Variants in odontogenic genes, such as the paired box 9 ( PAX9) [4] , axin inhibitor 2 ( AXIN2 ) [5] , ectodysplasin A ( EDA ) [6] , kringle domain-containing transmembrane protein 1 containing the kringle domain ( KREMEN1 ) [7] , MSX1 [8] , paired-like homeodomain transcription factor 2 paired ( PITX2 ) [9] , and wingless-type MMTV integration site family member 10 A ( WNT10A ) [10] genes result in arrested tooth development.…”
Section: Introductionmentioning
confidence: 99%
“…Tooth development is regulated by several genes and signaling pathways [3] . Variants in odontogenic genes, such as the paired box 9 ( PAX9) [4] , axin inhibitor 2 ( AXIN2 ) [5] , ectodysplasin A ( EDA ) [6] , kringle domain-containing transmembrane protein 1 containing the kringle domain ( KREMEN1 ) [7] , MSX1 [8] , paired-like homeodomain transcription factor 2 paired ( PITX2 ) [9] , and wingless-type MMTV integration site family member 10 A ( WNT10A ) [10] genes result in arrested tooth development.…”
Section: Introductionmentioning
confidence: 99%
“…[15] It has been reported that more than 80 genes were related to TA. [16] Variants in odontogenic genes, such as axis inhibition protein 2 (AXIN2), [17] muscle segment homeobox 1 (MSX1), [18] paired box 9 (PAX9), [19][20][21] wingless-type MMTV integration site family member 10 A (WNT10A), [22] tumor-protein 63 (TP63), [23] the human mutY homologue (MUTYH), [24] breast cancer 1 (BRCA1), [25] and ectodysplasin A (EDA) [26,27] have been related to dental agenesis. Interestingly, mutations in these genes may be associated with several cancer types.…”
Section: Introductionmentioning
confidence: 99%